Fabrication of polymeric optical waveguides - Shee, Yu Gang; Mohd. Kassim, Norazan; Mohammad, Abu Bakar; Ibrahim, Mohd. Haniff (IEEE, 2004)

(untitled)
This paper reports the fabrication of polymeric optical waveguides. Single mode planar slab waveguides and straight waveguides had been fabricated using the organic polymer B-staged bisbenwcyclohutene (BCB) from DOW Chemical. A low cost fabrication method, chemical etching is used to form the waveguides on BK-7 glass substrates. The processing conditions required for the fabrication of single mode optical waveguides were thoroughly been investigated and presented in this paper.